PENGEMBANGAN MEDIA PEMBELAJARAN KEANEKARAGAMAN HAYATI BERBASIS SCIENTIFIC TERINTEGRASI DALAM BLOGSPOT UNTUK SISWA SMA NEGERI 1 TELUKDALAM - Nofamataro Zebua (Universitas Nias Raya, 2022)
The limited availability of books and the lack of utilization of biology learning media by teachers is one of the serious obstacles in learning activities. This study aims to develop biodiversity learning media. This type of research is research and development using PLOMP development method. This study was tested on the students of Class XI SMA Negeri 1 Telukdalam totaling 20 people. To standardize the product, it is carried out through three stages of testing, namely; validity test, practicality test, and effectiveness test. The instrument used is to distribute the assessment questionnaire using likert scale and evaluation test questions to determine the cognitive learning outcomes of students. The results showed that the scientific-based blogspot media on biodiversity material was very valid with a percentage of 94.7% and feasible to use. The average value of practicalities assessed by teachers (3.6) and students (3.55) is in the category of very practical. The results of student motivation were at 86.18% with an average value of 87.7% improved cognitive learning outcomes compared to the value before using the media with an average score of 57.2 in the sufficient category. Suggestions proposed by researchers are 1) biology subject teachers should be able to use scientific-based blogspot media as a learning medium in the teaching and learning process because it can increase student interest and motivation. 2) through this learning media, hopefully students can broaden their horizons regarding biology learning on biodiversity materials. 3) for further researchers, this scientific-based blogspot media can be used as a reference in relevant research.